Mitral valve prolapse: clinical variants, current understanding - A. V. Klemenov (Лечащий Врач, 2021)
The article covers clinical diversity of mitral prolapse, deliberating ambiguous prognosis in patients with mitral valve prolapse (MVP) and different tactics of their management. The greatest attention is paid to primary MVP as the only variant of mitral prolapse claiming nosological independence. The origin of a primary MVP as a consequence of congenital mesenchymal inferiority in the framework of hereditary connective tissue disorders is considered.